THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON THE LECTURERS’ PERFORMANCE IN INSTITUTE TECHNOLOGY BUSINESS AAS INDONESIA - Sumadi Sumadi; Tira Nur Fitria (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Transformational leadership is leadership where the leaders can inspire, direct and move followers to make change through empowerment in achieving certain goals. It can be related to the employee performance results of one's work in an organization. The research was to know the influence behavior of transformational leadership on the Sharia Economics’ lecturer’s performance in ITB AAS Indonesia. This research used quantitative research. This research was carried out using a questionnaire and interview. This sample of this research involved several Sharia Economics’ lecturers. The result analysis shows that the aspects of transformational leadership such as idealized influence, inspirational motivation, intellectual stimulation, and individualization consideration have an effect of 87.1% on the performance appraisal of the lecturers’ performance of ITB AAS Indonesia. Transformational leadership is influential on the performance of lecturers at ITB AAS Indonesia after research and statistical tests were carried out. Based on these findings, it can be concluded that lecturers’ performance is positively influenced by transformational leadership.